Recommendations to design environmental monitoring in the European bullhead, Cottus sp., based on reproductive cycle and immunomarker measurement. Issue 2 (30th June 2015) - Bado-Nilles, Anne; Villeret, Mélanie; Geffard, Alain; Palluel, Olivier; Blanchard, Christophe; Le Rohic, Cindy; Besson, Sylvain; Porcher, Jean-Marc; Minier, Christophe; Sanchez, Wilfried
Highlights: This study aimed to determine the link between reproductive status and immune activity in Cottus sp. Immune capacities were more correlated with environmental factors than reproduction. Autumn was the best season for environmental immunomonitoring. Abstract: European bullhead is a relevant fish species to assess adverse effects of environmental stress on wild fish. Nevertheless, their complex reproductive cycle is very different between sites and could interfere with many physiological processes. Thus, prior to use biomarker to statute on environmental quality of rivers, we wanted to characterize reproductive profile (spawn number, GSI, gonad development). The major results demonstrated that the two types of reproductive cycle shown were strongly correlated to water temperature variation. In a second time, even if innate immunomarkers are highly relevant on biomonitoring program, hormonal variation seems to impact severely their responses. Thus, the link between reproductive status and immune activity (leucocyte distribution, cellular mortality, respiratory burst, phagocytosis activity) must also be study. Nonetheless, in the present work, immune capacities seems to be more correlated with season and environmental factors than reproduction.